Hubungan Islam dan Negara dalam Perspektif Abdurrahman Wahid - Raniasati, Rifani; Ngaisah, Zulaikha Fitri Nur; Adinugraha, Hendri Hermawan; Nasarruddin, Razie Bin (Aqlania, 2022)
Abdurrahman Wahid is one of the figures that can align the relationship between religion and state ideology within the framework of Indonesian plurality. Theological thoughts in Indonesia have caused many conflicts. One of them is in Islam, where groups appear in the name of Islam and are anti-Pancasila and anti-diversity. Such movements have often been eradicated. However, it will re-emerge in a new form and never seems to die. This is due to the inability of the people to interpret Islamic law with the right measurement tools. The researcher seeks to explore Gus Dur's thoughts with a dialectical focus on the concepts of religion and state, especially the relationship between Islam. From this thought, it is hoped that it can become one of the references in efforts to create harmony in the relationship between religion and the state. So that in the future anti-diversity and Pancasila movements will no longer be the cause of conflict between state ideology and religion. This research is a type of library research, namely research using library data sources. This research uses qualitative with historical and philosophical approaches. Data is sourced from primary data and secondary data. Primary data comes from Gus Dur's books and secondary data comes from other literary sources. Let religious diversity be the difference, but the plurality of this society must be equated in the attitude of humanism or human values. Religion (read: Islam) adapts as necessary to ideology and state laws, without having to let go of the transcendental principles that have been established by Allah SWT. Islam that needs to be upheld is Islam as Rahmatan Lil Alamin where there is the existence of implementing basic Islamic values ​​such as peace, humanity, tolerance, and so on. The absence of an Islamic state does not mean that Muslims must live individually. However, they can form a community and formulate the obligatory collective religion they profess.